Tuning the Electrocrystallization Parameters of Semiconducting Co[TCNQ]2-Based Materials To Yield either Single Nanowires or Crystalline Thin Films - Nafady, A.; Bond, A.; Bilyk, A.; Harris, A.; Bhatt, A.; O'Mullane, A.; De Marco, Roland (American Chemical Society, 2007)
Abstract:Electrocrystallization of single nanowires and/or crystalline thin films of the semiconducting and magnetic Co[TCNQ]2(H2O)2 (TCNQ = tetracyanoquinodimethane) charge-transfer complex onto glassy carbon, indium tin oxide, or metallic electrodes occurs when TCNQ is reduced in acetonitrile (0.1 M [NBu4]- [ClO4]) in the presence of hydrated cobalt(II) salts. The morphology of the deposited solid is potential dependent. Other factors influencing the electrocrystallization process include deposition time, concentration, and identity of the Co2+ (MeCN) counteranion. Mechanistic details have been elucidated by use of cyclic voltammetry, chronoamperometry, electrochemical quartz crystal microbalance, and galvanostatic methods together with spectroscopic and microscopic techniques. The results provide direct evidence that electrocrystallization takes place through two distinctly different, potential-dependent mechanisms, with progressive nucleation and 3-D growth being controlled by the generation of [TCNQ]- at the electrode and the diffusion of Co2+ (MeCN) from the bulk solution. Images obtained by scanning electron microscopy reveal that electrocrystallization of Co[TCNQ]2(H2O)2 at potentials in the range of 0.1-0 V vs Ag/AgCl, corresponding to the [TCNQ]0/- diffusion-controlled regime, gives rise to arrays of well-separated, needleshaped nanowires via the overall reaction 2[TCNQ]- (MeCN) + Co2+ (MeCN) + 2H2O h {Co[TCNQ]2(H2O)2}(s). In this potential region, nucleation and growth occur at randomly separated defect sites on the electrodesurface. In contrast, at more negative potentials, a compact film of densely packed, uniformly oriented, hexagonal-shaped nanorods is formed. This is achieved at a substantially increased number of nucleation sites created by direct reduction of a thin film of what is proposed to be cobalt-stabilized {(Co2+)([TCNQ2]-)2} dimeric anion. Despite the potential-dependent morphology of the electrocrystallized Co[TCNQ]2(H2O)2 and the markedly different nucleation-growth mechanisms, IR, Raman, elemental, and thermogravimetricanalyses, together with X-ray diffraction, all confirmed the formation of a highly pure and crystalline phase of Co[TCNQ]2(H2O)2 on the electrode surface. Thus, differences in the electrodeposited material are confined to morphology and not to phase or composition differences. This study highlights the importance of the electrocrystallization approach in constructing and precisely controlling the morphology and stoichiometry of Co[TCNQ]2-based materials.